2012
DOI: 10.1002/nur.21507
|View full text |Cite
|
Sign up to set email alerts
|

Older homebound women's perceived risk of being unable to reach help quickly: Influence of situations involving age‐peers

Abstract: The purpose of this facet of a longitudinal descriptive phenomenological study of the experience of reaching help quickly for older homebound women was to explore the personal-social context (life-world) of situations when age-peers had needed to reach help quickly (RHQ). Twenty-five women aged 85–95 (13 subscribers to a personal emergency response system and 12 non-subscribers) reported 80 peer situations. Life-world was characterized by sharing with peers the risk of being unable to RHQ. Knowledge of peer si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The most stated reason for getting a PERS was the possibility of getting help fast in an emergency [ 27 , 30 , 32 , 33 , 35 , 38 - 40 ]. Living in isolation, poor mobility, experiences with hospital stays after a “long lie” following a fall, and concern for personal safety were all catalysts for acquiring the alarm [ 29 , 35 , 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most stated reason for getting a PERS was the possibility of getting help fast in an emergency [ 27 , 30 , 32 , 33 , 35 , 38 - 40 ]. Living in isolation, poor mobility, experiences with hospital stays after a “long lie” following a fall, and concern for personal safety were all catalysts for acquiring the alarm [ 29 , 35 , 37 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that some users would not activate the PERS even in emergencies [ 9 , 30 , 34 , 48 ]. Reasons given were as follows: “wanted to manage on their own,” “forgot,“ “call neighbor,” “see if it passes,” “don’t want to be dragged off to hospital,” “afraid to bother,” “called 911,” “unsure whether serious enough emergency,” “don’t want strangers in the house,” and “unsure of helpers’ qualifications” [ 16 , 29 , 32 , 38 , 43 ]. Many respondents never felt in need, and therefore never activated their alarm [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many overseas studies have found that the prevalence of homebound women is significantly higher than men. The reasons could be complex, [ 18 , 21 ] which may be due to diet habits, sexual hormone levels, work stress, and social pressure, and also due to the profound influence on their behaviors by the traditional role of a man and a woman in the family, that is, men are encouraged to work outside, while women are encouraged to work at home. Hence men preferred social activities outside the family, while women focused more on family and children and stayed at home.…”
Section: Discussionmentioning
confidence: 99%